Managing multiple-supplier project teams in new software development - Jiang, James J.; Klein, Gary; Tsai, Jacob Chia-An; Li, Yuzhu (International journal of project management, 2018)
Goal and resource interdependence are vital elements in structuring new software development programs distributed across multiple organizations. Yet, we know little about how the precursor interdependencies affect collaborative behaviors among the inter-organizational projects. The objective of this study is to examine the collaborative structure of multiple projects in a supplier network, particularly in the context of new software externally developed. Based on social interdependence theory (SIT), we explore the impacts of goal interdependence and resource interdependence among the inter-firm software project teams on inter-project cooperation and coordination. The focus is on the combined effect of both interdependencies to determine if they contribute additively to the promotive behaviors of cooperation and coordination. Based on a sample of matched key informants for 149 business-to-business (B2B) product development programs in China, both goal interdependence and resource interdependence have a positive influence on coordination and cooperation as suggested in the literature. However, goal and resource interdependence interact such that the effects are not additive, but that the presence of goal interdependence reduces the effect of resource interdependence. •Goal or resource interdependence alone is inadequate to lead to promotive behaviors.•The interactive effects of goal and resource interdependence are not additive.•Construction of goals is critical to ensure desired performance.